Extending the theory of the multinational enterprise: internalization and strategic management perspectives - Rugman, Alan M; Verbeke, Alain (Journal of International Business Studies, 2003)
This paper assesses the continued relevance of Buckley and Casson's (1976) book on The Future of the Multinational Enterprise (MNE), against a background of increasing criticism of transaction-cost-related scholarly work. We demonstrate that the ‘schism’ that can currently be observed in the field between international business and international management is misguided, as the transaction cost/internalization school may offer useful insights to both management scholars and managers. For this to occur, however, it is necessary first to extend the empirical scope of transaction-cost-based reasoning to include the functioning of differentiated network MNEs. The paper suggests that Buckley and Casson's book still represents a beacon of clarity and a superb starting point for the study of the MNE, even if the complexity of this governance structure has grown far beyond what any international business scholar or even international management scholar could have predicted 25 years ago.